Functional Analysis of RUNX2 Mutations in Japanese Patients with Cleidocranial Dysplasia Demonstrates Novel Genotype-Phenotype Correlations - Yoshida, Taketoshi (The American Society of Human Genetics, 2002)
Cleidocranial dysplasia (CCD) is an autosomal dominant heritable skeletal disease caused by heterozygous mutations in the osteoblast-specific transcription factor RUNX2. We have performed mutational analysis of RUNX2 on 24 unrelated patients with CCD. In 17 patients, 16 distinct mutations were detected in the coding region of RUNX2: 4 frameshift, 3 nonsense, 6 missense, and 2 splicing mutations, in addition to 1 polymorphism. The missense mutations were all clustered within the Runt domain, and their protein products were severely impaired in DNA binding and transactivation. In contrast, two RUNX2 mutants had the Runt domain intact and remained partially competent for transactivation. One criterion of CCD, short stature, was much milder in the patients with the intact Runt domain than in those without. Furthermore, a significant correlation was found between short stature and the number of supernumerary teeth. On the one hand, these genotype-phenotype correlations highlight a general, quantitative dependency, by skeleto-dental developments, on the gene dosage of RUNX2, which has hitherto been obscured by extreme clinical diversities of CCD; this gene-dosage effect is presumed to manifest on small reductions in the total RUNX2 activity, by approximately one-fourth of the normal level at minimum. On the other hand, the classic CCD phenotype, hypoplastic clavicles or open fontanelles, was invariably observed in all patients, including those with normal height. Thus, the cleidocranial bone formation, as mediated by intramembranous ossification, may require a higher level of RUNX2 than does skeletogenesis (mediated by endochondral ossification), as well as odontogenesis (involving still different complex processes). Overall, these results suggest that CCD could result from much smaller losses in the RUNX2 function than has been envisioned on the basis of the conventional haploinsufficiency model.